HABIB HUSEIN JA'FAR ALHADAR'S DA'WAH RHETORIC STYLE ON YOUTUBE - Bahrun Mahabi (QAULAN: Journal of Islamic Communication, 2023)
Communication is a relationship of delivery interaction we do daily. If the communicant does not know what the communicator is conveying, rhetoric is needed so that what we want to convey will not be in vain. The relationship between rhetoric and da'wah is the ability to use language to generate thoughts and feelings to invite listeners to good. Based on this uniqueness, researchers ask the following question: What is the style of language based on word choice, tone, and sentence structure Habib Husein Ja'far Alhadar via Youtube Gita Wirjawan, episode Habib Husein Ja'far: Saleh Akal and Social, Not Just Ritual? This study uses Gorys Keraf's theory, which discusses Language Style. It uses a qualitative research approach with the type of research using data collection techniques through observation and documentation. The results of this study show that: 1). The rhetorical style of da'wah Habib Ja'far Husein Alhadar, Gorys Keraf's rhetorical perspective on language style based on language choice is unofficial language style and conversational language style. 2). Based on tone is a simple, polite, humorous tone. 3) Based on sentence structure is anticlimactic sentence structure and repetition.